2021
DOI: 10.3390/medicina57101114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Recovery after Manual and Target-Controlled Infusion of Remifentanil in Bariatric Surgery

Abstract: Background and Objectives: Early postoperative recovery after surgery is a key point for patients’ safety and comfort. Moreover, operating room turnover depends on recovery time. Our aim was to assess which method of remifentanil administration, manual (MI) or target-controlled infusion (TCI), could reduce patient time in recovery room. In this study, patients’ recovery times were registered and compared among the groups. Materials and Methods: We enrolled 31 morbidly obese patients in this prospective study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the future, if the dose of remifentanil is adjusted using pain monitoring equipment, an objective and highly reproducible study can be performed. Additionally, the intraoperative dose of remifentanil was smaller than in previous studies [ 15 , 19 , 22 ]. However, the dose of remifentanil for maintaining general anesthesia is suggested as 0.05–0.2 µg/min/kg, and the dose in our study also corresponds to this range.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the future, if the dose of remifentanil is adjusted using pain monitoring equipment, an objective and highly reproducible study can be performed. Additionally, the intraoperative dose of remifentanil was smaller than in previous studies [ 15 , 19 , 22 ]. However, the dose of remifentanil for maintaining general anesthesia is suggested as 0.05–0.2 µg/min/kg, and the dose in our study also corresponds to this range.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies comparing TCI and manual infusion as remifentanil injection methods reported that the total dose of remifentanil was higher in the manual infusion group [ 15 , 19 ]. In our study, the higher dose of remifentanil infusion during surgery in the T group may have resulted from the large amount of remifentanil administered immediately before tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%